Effect of the sanitary situation of the poultry house on the larval stages of endoparasites in the intermediate hosts and on the productive performance - Gorrín A., Gabriel (2018)
The objective of the study was to evaluate the effect of the health status of poultry houses on the prevalence of larval stages of endoparasites in intermediate hosts and on the productive behavior of 55-week-old White Leghorn laying hens for eight weeks. Two treatments were designed (T1 and T2) with 486 chickens each (three replicas of 162 birds), according to the hygienic quality of two chicken houses (dust levels in the floor, puddles in excreta towers, feathers and broken eggs in the floor and corridors, presence of wild birds, population of insects). Every 15 days (four samplings) 1 kg of excreta per replica was collected from the excreta towers to quantify and classify the intermediate hosts. All insects and arthropods were identified, and the presence of nematode larvae and larval cysts was quantified. The intestines of 15 birds (T1=7; T2=8) were collected for the identification of endoparasites. The extension of the infestation was determined, and the productive variables were estimated (production of total eggs and per bird, percentage of egg laying, conversion, viability, and external quality of the egg). The results indicated that the sanitary situation of the chicken house with poor hygienic conditions (T2) positively influenced the populations of intermediary hosts of cestodes and in a greater production of eggs with dirty, stained, and broken shells. Alphitobius diaperinus was the coleopter with the highest presentation and with the highest intensity of infestation by Subulura suctoria.